Legal Analysis of the Regulation and Protection of Consumer Rights in Murabahah Financing - Marta Dwi Astuti; Masnunah Alfatunnisa (Walisongo Journal of Sharia Economic Law, 2025)
Murabaha financing is one of the main instruments in Islamic banking in Indonesia, which has made a significant contribution to supporting the economic activities of the people. However, in practice, various problems are often encountered, particularly related to information transparency, legal certainty, and fairness for consumers. This study aims to analyze juridically how regulations in Indonesia govern and protect consumer rights in murabaha financing. The research method used is normative legal research with a legislative and conceptual approach, supported by secondary data in the form of laws, DSN-MUI fatwas, and academic literature. The results show that regulations in Indonesia have provided a basis for consumer protection, but there are still weaknesses in their implementation, particularly in the use of standard contracts and clauses that have the potential to harm consumers. This study concludes that there is a need to reformulate regulations to be more adaptive to consumer interests and in line with the principles of justice and maqashid al-shariah. Thus, this study provides theoretical and practical contributions to strengthening consumer protection in Islamic banking.